Para-aortic and Meningitis Tuberculosis: A Case Report - Reviono, Reviono; R, Sari Apriliana; Sutanto, Yusup Subagio; Soetejo, FX; Subandrio, Subandrio (Indonesian Journal of Medicine, 2019)
Background: In 2018, Indonesia was in third place as the country with the highest incidence of tuberculosis (TB) in the world. In addition to pulmonary TB, extrapulmonary TB cases are also quite large. Lymphadenitis of the aortic TB can cause a fatal risk if not treated immediately. This study aimed to explore the para-aortic and meningitis tuberculosis case in Klaten Hospital, Central Java.Case presentation: There was a 24-year-old woman with complaints of missing chest pain for 2 months, fear of seeing light (photophobia), and decreased consciousness. The patient was a referral from Klaten Hospital with a diagnosis of a mediastinal tumor. The chest radiograph shows a picture of homogeneous opacity in the anterior mediastinum. Bronchoscopy results show compression stenosis in 1/3 distal and blunt carina. After a sternotomy, it was obtained pus (pus) and tissue granuloma in the area of the aorta. After the rapid molecular test was carried out, the results showed that M tuberculosis detected. The results of histopathology of anatomical pathology show epitheloid tubercle and Datia Langhans cells that suggest an infection with M. tuberculosis. Therapy was done by giving a standard anti-tuberculosis drug, namely Rifampicin 450 mg, INH 300 mg, Ethambutol 1000 mg, and Pyrazinamide 1000 mg. The patient's condition improved marked by weight gain in 2 months.Conclusion: In the case of pulmonary masses (mediastinal tumors), we need to be aware of the possibility of cases of TB lymphadenitis because Indonesia is a country with a high prevalence of TB. This is because a slow diagnosis can lead to life-threatening conditions Keywords: Tuberculosis, para aorta lymphadenitis, meningitis TB, tumor mediastinum, sternotomyCorrespondence: Reviono. Department of Pulmonology and Medical Respiration, Universitas Sebelas Maret Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: reviono@staff.uns.ac.id. Mobile: +62818474671.Indonesian Journal of Medicine (2019), 4(3): 201-210https://doi.org/10.26911/theijmed.2019.04.03.02